Маркетинговые подходы и инструменты самоорганизации сельской местности (Географический вестник=Geographical bulletin, 2017)
Рассматриваются вопросы выявления характера саморазвития сельской местности, ее основных параметров на основе современных маркетинговых подходов и методов, что имеет большое социально-экономическое значение для развития Пермского края. Показано, что, несмотря на некоторые рыночные достижения социально-экономического сектора сельской местности Пермского края, он по ряду объективных и субъективных причин не вышел из кризисного состояния.MARKETING APPROACHES AND TOOLS OF SELF-ORGANIZATION OF THE COUNTRYSIDEDevelopment of the countryside is a good opportunity to widen potential of the regions within global, dramatically progressive economy. Maintaining of the characteristics of the countryside and its main operation factors, based on the marketing approaches, has a crucial economic and social influence onPermregion. In this article it is shown that beyond some market achievements in the social and economic area of thePerm’s region countryside, it is still in the recession because of the several reasons.K e y w o r d s: region; area; market; agricultural; transform; product.